Informed breeding dispersal following stochastic changes to patch quality in a pond‐breeding amphibian. Issue 8 (12th May 2021) - Barrile, Gabriel M.; Walters, Annika; Webster, Matthew; Chalfoun, Anna D.
Abstract: The unidirectional movement of animals between breeding patches (i.e. breeding dispersal) has profound implications for the ecological and evolutionary dynamics of spatially structured populations. In spatiotemporally variable environments, individuals are expected to adjust their dispersal decisions according to information gathered on the environmental and/or social cues that reflect the fitness prospects in a given breeding patch (i.e. informed dispersal). A paucity of empirical work limited our understanding of the ability of animals to depart from low‐quality breeding patches and settle in high‐quality breeding patches. We examined the capacity of individuals to respond to stochastic changes in habitat quality via informed breeding dispersal in a pond‐breeding amphibian. We conducted a 5‐year (2015–2019) capture–recapture study of boreal toads Anaxyrus boreas boreas ( n  = 1, 100) that breed in beaver ponds in western Wyoming, USA. During early spring of 2017, an extreme flooding event destroyed several beaver dams and resulted in the loss of breeding habitat. We used multi‐state models to investigate how temporal changes in pond characteristics influenced breeding dispersal, and determine whether movement decisions were in accordance with prospects for reproductive fitness. Boreal toads more often departed from low‐quality breeding ponds (without successful metamorphosis) and settled in high‐quality breeding ponds (with successful metamorphosis). Movement decisions were context‐dependent and associated with pond characteristics altered by beaver dam destruction. Individuals were more likely to depart from shallow ponds with high vegetation cover and settle in deep ponds with low vegetation cover. The probability of metamorphosis was related to the same environmental cues, suggesting that boreal toads assess the fitness prospects of a breeding patch and adjust movement decisions accordingly (i.e. informed breeding dispersal). We demonstrated that stochastic variability in environmental conditions and habitat quality can underpin dispersal behaviour in amphibians. Our study highlighted the mechanistic linkages between habitat change, movement behaviour and prospects for reproductive performance, which is critical for understanding how wild animals respond to rapid environmental change. Abstract : The authors study demonstrated that stochastic variability in environmental conditions and patch quality can underpin dispersal behaviour in amphibians. They highlighted the mechanistic linkages between habitat change, movement behaviour and reproductive potential, which is critical for understanding how wild animals respond to rapid environmental change.